ANALISISIS LAPORAN KONSOLIDASI KEUANGAN TERHADAP EVALUASI KINERJA KEUANGAN PT. SUMBER ALFARIA TRIJAYA TBK MELALUI RASIO PROFITABILITAS PERIODE 2019 – 2023 - Anggarda Putra, Alvin; Indra Sholahudin, Muhamad; Fajar, Ichsan; Mbeppa, Yulita; Santoso, Budi (Universitas Muhammadiyah Metro, 2025)
This study aims to evaluate the financial performance of PT. Sumber Alfaria Trijaya Tbk using profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE), over the 2019–2023 period. The research employs a descriptive quantitative approach utilizing secondary data from the company's financial statements obtained through the Indonesia Stock Exchange. The results indicate that the company's ROA increased from 4.75% in 2019 to 10.17% in 2023, reflecting improved efficiency in asset utilization. However, ROE showed fluctuations, with a decline in 2023 despite increased net profit, indicating the need for more optimal equity management. Overall, although the company's financial performance is relatively good, more effective asset and equity management strategies are required to enhance profitability sustainably.